Measurement of the zygomatic bone and pilot hole technique for safer insertion of zygomaticus implants. Issue 1 (January 2016) - Takamaru, N.; Nagai, H.; Ohe, G.; Tamatani, T.; Sumida, K.; Kitamura, S.; Miyamoto, Y.
Abstract: The zygomaticus implant was developed for patients with severe bone resorption of the posterior maxilla. These may eliminate or minimize the need for bone grafting. Although the zygomaticus implant has shown a remarkable success rate in this difficult-to-treat patient population, the method requires an advanced surgical technique and carries an increased risk of complications. There have been few anatomical studies on the zygomatic bone in relation to the insertion of zygomaticus implants. The height and thickness of the zygomatic bone for the insertion were measured in this study. The thickness at the 90° angle point, where the upper margin of the zygomatic arch and the temporal margin of the frontal process of the zygomatic bone intersect and where the apex of the implant penetrates, was found to be 1.8 ± 0.4 mm; this gradually increased inferiorly and anteriorly. Thus, the penetration point of the apex of the zygomaticus implant should be located more inferoanterior to the 90° angle point, as the thickness in this region is thinner than the diameter of the implant. Based on the results of this study, a newer and safer insertion method for the zygomaticus implant using a drill guide is proposed.